The efficiency of wastewater purification from chromium (III) Ions by natural clay sorbents - Sakalova, Halyna; Vasylinych, Tamara; Petrushka, Kateryna; Stocaluk, Oleh; Chornomaz, Nataliya; Sakalova, Halyna; Vasylinych, Tamara; Petrushka, Kateryna; Stocaluk, Oleh; Chornomaz, Nataliya (Lviv Politechnic Publishing House, 2018)
The study confirmed the promising application of clays mineral sorbents for wastewater purification from Chromium (III) ions. The process of chromium ions absorption from drain water by means of natural mineral sorbent glauconite in static conditions was investigated. The adsorption processes were adapted to the known technological schemes of sewage and polluted surface water purification from heavy metal ions. There were measured the technological aspects of water purification by using adsorption on natural dispersed sorbents.
Keywords: natures dispersed sorbents; sewage; ions of heavy metals; bentonite and glauconite clays